Research on sustainable development of agricultural product cold chain logistics under public safety emergencies - He, Yuze; Liu, Mingfei (Frontiers in Sustainable Food Systems, 2023)
Under a sudden public security event, as agricultural cold chain logistics has the characteristics of many participating subjects and wide spatial and temporal distribution, it is extremely vulnerable to shocks. Even minor disruptions in logistics can result in a significant impact on the daily lives of residents. Therefore, improving the resilience of agricultural cold-chain logistics is crucial for sustainable development. This paper studies the sustainable development path of agricultural cold chain logistics from a resilience perspective. Through rooting theory, the process of resilience in agricultural cold chain logistics under sudden public safety events is explored. Based on the knowledge meta-model, three elements of resilience events, resilient subjects, and resilience measures are used to contextualize the resilience process, and finally, using Bayesian networks and fuzzy set theory, a contextual derivation model of the resilience process of agricultural cold chain logistics under sudden public safety events is created. The results show that the resilience process of sustainable development consists of a resistance period, an adaptation period, a readjustment period, and an innovation period, during which the government and enterprises jointly take measures to effectively resist the impact of public emergencies, and further enhance the resilience through innovative development to ensure the sustainable development of agricultural cold chain logistics.